2014
DOI: 10.3109/0284186x.2013.879608
|View full text |Cite
|
Sign up to set email alerts
|

Human papilloma virus detection and typing in 334 lung cancer patients

Abstract: Background. Unlike cervical, anogenital and oropharyngeal cancers, where high-risk human papillomavirus (hrHPV) has long been known to play a major role, a causative link between HPV and lung cancer has been investigated for decades with discrepant results. Methods. Lung cancer patients eligible for surgical treatment were tested for the presence of HPV-DNA in excised, fresh frozen lung tumor tissue. Patients that tested positive were further examined for the presence of HPV-DNA in adjacent normal lung parench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…However, a review of the clinical history revealed a potential source of metastasis for all 5 patients, such as head and neck and cervical SqCC. Recently published data from a Norwegian population found HPV DNA (PCR on fresh-frozen tissue) in 13 of 334 lung cancers (12 hrHPV cases and 1 HPV11 case of unknown histologic type) [21]. These cases were predominantly from male patients (10/12) and ADCs (11/13).…”
Section: Discussionmentioning
confidence: 95%
“…However, a review of the clinical history revealed a potential source of metastasis for all 5 patients, such as head and neck and cervical SqCC. Recently published data from a Norwegian population found HPV DNA (PCR on fresh-frozen tissue) in 13 of 334 lung cancers (12 hrHPV cases and 1 HPV11 case of unknown histologic type) [21]. These cases were predominantly from male patients (10/12) and ADCs (11/13).…”
Section: Discussionmentioning
confidence: 95%
“…In total, 5.2% of the worldwide cancer burden is attributable to HPV (Yue et al 2013). HPV DNA has been detected in tumour tissues of patients with head and neck cancers (Ringstrom et al 2002), oral cancer (Ritchie et al 2003), oesophageal cancer (Dai et al 2007), some skin cancers (Connolly et al 2014), and lung cancer (Sagerup et al 2014, Zhai et al 2015). Over the last few years, a possible correlation between HPV infection and colorectal cancer (CRC) has been suggested, based on several researchers detecting HPV DNA in these cancers, using different techniques (Buyru et al 2006, Damin et al 2007, Pérez et al 2010, Chen et al 2012).…”
mentioning
confidence: 99%
“…21 Although smoking habits is the strongest factor linked to lung cancer, the incidence of the disease among non-smokers has increased. 22 In addition to smoking, other factors are also related to lung cancer such as occupational exposure, previous lung disease and diet among others are attracting the attention of the physicians to patients who do not smoke. [22][23][24] Based on this, we can suppose that additional factors might be the cause of the disease and they can function independently or in combination with the well-known factors.…”
Section: Lung Cancer: Current Aspectsmentioning
confidence: 99%
“…22 In addition to smoking, other factors are also related to lung cancer such as occupational exposure, previous lung disease and diet among others are attracting the attention of the physicians to patients who do not smoke. [22][23][24] Based on this, we can suppose that additional factors might be the cause of the disease and they can function independently or in combination with the well-known factors. 23,25 Regarding the histology, lung cancer is classified into two main groups: Small Cell Lung Cancer (SCLC) and Non-Small Cell Lung Cancer (NSCLC).…”
Section: Lung Cancer: Current Aspectsmentioning
confidence: 99%
See 1 more Smart Citation